Effectiveness of micronutrient dietary intake and micronutrients fortifed milk to improve serum zinc concentrations of primary school children - Van, Tran Khanh; Nga, Tran Thuy; Hiep, Nguyen Xuan; Tu, Nguyen Song; Tu, Nguyen Tran Ngoc (Tạp chí Y học Dự phòng, 2021)
Micronutrient dietary intake of primary school children was evaluated at baseline survey. Then the randomized community intervention trial with pre- and post-intervention evaluation aims to evaluate effectiveness of micronutrient dietary intake and micronutrients fortified milk to improve serum zinc concentrations of primary school children. The two common types of milk on the market are fresh milk and reconstituted milk which were used as food vehicles to fortify 21 different vitamins and minerals and given to 2 groups of school children at a dose of 2 boxes of 180 ml/day, 7 day/ week for 6 months. Each group drank one kind of milk. Control group did not drink milk during the intervention. After the end of the intervention, serum zinc concentration in the two intervention groups improved significantly compared to the baseline (p <0.01). The serum zinc concentrations were increased by 0.65±3.13 μmol/L and 0.75±3.49 μmol/L in the group of drinking micronutrient fortified fresh milk and the group of drinking micronutrients fortified reconstituted milk, respectively Zinc concentration after 6 months and difference of zinc concentration between baseline and 6 months after intervention in intervened groups were improved significantly compared to those of the control group (p <0.05).